2018
DOI: 10.5658/wood.2018.46.6.726
|View full text |Cite
|
Sign up to set email alerts
|

Static Bending Performances of Cross-Laminated Wood Panels Made with Tropical and Temperate Woods

Abstract: In this study, for using effectively domestic (temperate) small and medium diameter logs as a wooden floorboard, cross-laminated wood panels were manufactured using domestic larch and tulip woods as a base material for teak and merbau wood flooring, and static bending strength performances were measured to investigate the applicability as the base materials of wooden flooring in place of plywood. Static bending MOE was much influenced by the strength performances of the top layer lamina than that of the lamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…CLT and ply-lam CLT, which showed an equivalent level, were subjected to an independent t-test, and as a result (t = -1.056, p=0.305), no significant difference in MOR according to the materials composition of CLT and Ply-lam CLT could be confirmed. MOR showed differences depending on the composition of the materials, and Byeon et al (2018) reported that MOR is affected by the strength of materials used for the core and bottom layers. Unlike UOE, MOR showed a difference because the strength was different depending on plywood, lumber, and arrangement direction among the composition materials.…”
Section: Bending Propertiesmentioning
confidence: 99%
“…CLT and ply-lam CLT, which showed an equivalent level, were subjected to an independent t-test, and as a result (t = -1.056, p=0.305), no significant difference in MOR according to the materials composition of CLT and Ply-lam CLT could be confirmed. MOR showed differences depending on the composition of the materials, and Byeon et al (2018) reported that MOR is affected by the strength of materials used for the core and bottom layers. Unlike UOE, MOR showed a difference because the strength was different depending on plywood, lumber, and arrangement direction among the composition materials.…”
Section: Bending Propertiesmentioning
confidence: 99%